Performance of simple irrigation scheduling calendars based on average weather data for annual ryegrass - Fessehazion, Melake K; Annandale, John G; Everson, Colin S; Stirzaker, Richard J; van der Laan, Michael; Truter, Wayne F; Abraha, Amanuel B (African journal of range & forage science, 2014)
Poor irrigation management in pastures can lead to yield and quality reduction as well as loss of income through extra pumping and leaching of nitrate fertiliser. A number of irrigation scheduling techniques of varying levels of sophistication have been developed over the years to address limited irrigation water availability and maximise productivity. Despite this, the adoption of irrigation scheduling tools by farmers remains low. The objective of this study was to assess the use of simple irrigation scheduling calendars based on average weather data to improve irrigation management in ryegrass. The calibrated Soil Water Balance (SWB) model was used to generate simple irrigation calendars and assess effectiveness for different scenarios by mechanistically simulating water dynamics and pasture growth. Scheduling irrigation using the calendars gave similar irrigation applications, water losses and yields compared to a more scientific real-time scheduling (in response to soil water depletion by the crop). While site-specific irrigation scheduling calendars can easily be generated by consultants and irrigators, even simpler monthly estimates of average daily water use can also be useful. Application of calendars by farmers is encouraged to improve water and nutrient use efficiency of irrigated pastures, if real-time irrigation scheduling is not employed.